РАСЧЕТ ПАРАМЕТРОВ УНИВЕРСАЛЬНОГО ФИЛЬТРА ВЫСШИХ ГАРМОНИК ДЛЯ СИСТЕМ С МНОГОПУЛЬСНЫМИ ВЫПРЯМИТЕЛЯМИ - Волков , И.В.; Каршенов , Д.П.; Подольный , C.В. (Інститут електродинаміки НАН України, Київ, 2014)
The calculation model of universal filter of high harmonics is researched. The electrical circuitry of this filter was developed in the Institute of Electrodynanics of NAS Ukraine and patented in the USA and other countries. It differs of known ones by using a mutual inductance between winding of reactor. The electrical system load in the model is a multipulse converter represented with the current sources. Besides the input voltage sources are assumed to be under harmonic distortion what has been considered by means of multi voltage source model. The analytical method was proposed for finding filter parameters and respective branch currents. References 8, figures 3.